Application of Constructivist Learning Theory in Engineering Drawing Teaching under the Blended Learning Model - Li, Wenyong (Pacific International Journal, 2024)
With the rapid development of educational informatization, the blended teaching model has been increasingly widely used in the field of education due to its advantages of flexibility, personalization and efficiency. This paper aims to explore the application of constructivist learning theory in engineering drawing teaching under the blended teaching model. By analyzing the core ideas of constructivist learning theory and the characteristics of blended teaching model, the relationship between the two is found, and their applicability in engineering drawing teaching is analyzed in detail. This paper proposes specific teaching strategies and verifies their effectiveness and feasibility through actual teaching cases. Practice has proved that the blended teaching model combined with constructivist learning theory can significantly improve the teaching quality of engineering drawing courses. Students can not only master basic knowledge in autonomy, collaboration, sharing and reflection, but also improve their spatial imagination, hands-on ability and innovation ability. At the same time, the role of teachers has also changed from knowledge transmitters to helpers and promoters of students’ active construction of meaning, which has promoted effective interaction and common development between teachers and students. In addition, this theoretical research also provides new perspectives and ideas for the reform of engineering drawing teaching.